Trends in the Internet of Things (IoT) and Influence on the Industries’ Progress - Zeynvand Lorestani, Vahid (International Journal of Engineering and Management Sciences, 2020)
This research aims to investigate the critical role of the Internet of Things in the future of industries’ progress. For this purpose, a survey of 250 top managers across 13 industries has conducted. The objective was to find their view of point about what short and mega trends, in which sector will have the most considerable influence in the five years as well as 30 years ahead. Moreover, various technologies are also identified that will have the most importance in the future according to the majority of the respondents, such as Internet of things, Automation and Artificial Intelligence, and, on the other hand, the segments that capital expenditure is currently being directed towards, such as Energy Efficiency and Personalisation of Services.